Firms under pressure: International trade and social activism - Claudius Löhnert (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2022)
Activists denouncing firms for what they consider unethical conduct (e.g., poor treatment of labor or practices that are harmful to the environment) often pressure firms through consumer boycotts. This paper presents a model of international trade with heterogeneous firms and endogenous campaigns conducted by social activists. Being the target of campaigns damages the reputation of a firm, reducing the perceived quality and therefore sales of its variety. Campaigns require funding by consumers who support the activists' mission. The paper analyzes the effect of such demand-reducing campaigns on firms. It identifies a feedback effect of campaigns that increases mark-ups in the presence of social activism, which stems from large firms attracting more campaigns while campaigns also decrease sales. The paper further shows that social activism reduces the elasticity of bilateral trade flows with respect to trade costs.
Keywords: F12; F61; L11; L31; O35; 330; international trade; heterogeneous firms; gravity; consumer boycotts; NGOs; campaigns; social activism